ECONOMIC IMPACT OF INSTITUTING SMOKING PROHIBITIONS IN NEW YORK (Tufts Archival Research Center, 2007)
Report on the economic impact smoking restrictions will have on New York. Covers the loss in both the private and public sectors as well as the social cost versus the private cost. Provides an overview of the proposed amendments to the New York Sanitary Code and concludes that a restriction of public smoking will cost the taxpayers and the small businesses in New York an estimated 623.7 million dollars.